Reuse of Chromium in Wastewater Treatment of Tannery - Salas Colotta, G. (2005)
The conventional method of chrome tanning, employed in Leather industry, results In a very poor exhaustion of chrome, thereby adding to the toxicity of the effluent. One of !he cleaner processing options recommended is that the chrome which is let out in the effluent, may be recovered for reuse to ensure not only economy of usage of chrome, but also effective management of this toxic substance. The waste water tannery contents 3 200 mg/L of Cr ( pH = 3,2 ). The methodology involves precipitation of chrome with an alkali with pH = 9, 1 and consume of O, 12 kg de MgO for one kg equivalen! de Cr2 Or The efficiency of recovery of Cr is 99,9 % (Cr water treatment 0,007 mg/L) with use Magnesia 65% MgO of purity. The supernatant liquor is separated, allowing the resulting precipitate to settle down. This precipitate is treated with sulfuric acid again, which can be reused.